The equation above holds true for positive integers and . Find .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Easier solution by Brian Moehring
Consider the following for ∣ x ∣ < 1 , we have:
1 + x + x 2 + x 3 + x 4 + x 5 + ⋯ 1 + 2 x + 3 x 2 + 4 x 3 + 5 x 4 + 6 x 5 + ⋯ 2 + 6 x + 1 2 x 2 + 2 0 x 3 + 3 0 x 4 + 4 2 x 5 + ⋯ 1 + 3 x + 6 x 2 + 1 0 x 3 + 1 5 x 4 + 2 1 x 5 + ⋯ = 1 − x 1 = ( 1 − x ) 2 1 = ( 1 − x ) 3 2 = ( 1 − x ) 3 1 = 1 − 3 x + 3 x 2 − x 3 1 Differentiating both sides w.r.t. x Differentiating both sides again Dividing both sides by 2
⟹ A + B = 3 + 1 = 4
My solution:
Consider the following for ∣ x ∣ < 1 , we have:
1 + x + x 2 + x 3 + x 4 + x 5 + ⋯ x 2 + x 3 + x 4 + x 5 + x 6 + x 7 + ⋯ 2 x + 3 x 2 + 4 x 3 + 5 x 4 + 6 x 5 + 7 x 6 + ⋯ 2 + 6 x + 1 2 x 2 + 2 0 x 3 + 3 0 x 4 + 4 2 x 5 + ⋯ 1 + 3 x + 6 x 2 + 1 0 x 3 + 1 5 x 4 + 2 1 x 5 + ⋯ = 1 − x 1 = 1 − x x 2 = ( 1 − x ) 2 2 x ( 1 − x ) + x 2 = ( 1 − x ) 2 2 x − x 2 = ( 1 − x ) 3 ( 2 − 2 x ) ( 1 − x ) + 4 x − 2 x 2 = ( 1 − x ) 3 2 = ( 1 − x ) 3 1 = 1 − 3 x + 3 x 2 − x 3 1 Multiplying both sides by x 2 Differentiating both sides w.r.t. x Differentiating both sides again Dividing both sides by 2
⟹ A + B = 3 + 1 = 4